Comparison of topical hypericum perforatum and metformin effectiveness in wound healing in streptozotocin-induced diabetic rats - Turhan, Banu; Sağlam, Sönmez; Yücel, Mücahit Osman; Dalaslan, Raşit Emin; Sungur, Mehmet Ali; Demir, Fatih; Karaduman, Zekeriya Okan; Arıcan, Mehmet (Frontiers in Endocrinology, 2025)
PurposeOur study aimed to assess and compare the effectiveness of topically applied Hypericum perforatum (HP) and metformin on wound healing in diabetic rats.MethodsThirty-two male Wistar rats (8–10 weeks old, 250 ± 50g) were divided into four groups of eight rats each: Control, Diabetes mellitus (DM), Metformin (Met), and HP. Diabetes was induced in all experimental rats except the control group using streptozotocin (STZ) (60mg/kg, intraperitoneal). A full-thickness skin defect was created in all rats. Two milliliters (ml) of sterile saline were administered to the Control and DM groups, two ml of metformin (10% gel, topical) to the Met group, and two ml of HP (olive oil extract) to the HP group, repeated every 24 hours for 14 days. The condition of the lesions was monitored on days 0, 3, 7, 10, and 14, and the extent of contraction and granulation tissue formation was documented. At the 14th day, the lesioned areas were examined histopathologically and immunohistochemically.ResultsThe baseline characteristics of the rats before the study showed no significant differences between the groups (p>0.05). The HP group had the smallest final wound size and the highest wound contraction percentages from day 0 to 14 (p<0.001 for both). There was no statistically significant difference among the groups in the collagen index (p=0.118). The fibroblast density scores in the DM group were significantly lower than those in the other groups (p=0.004). The hypertrophic index values of the HP group were the highest compared to the other groups (p=0.003). Although the HP and control groups exhibited higher TGF-β percentages and H scores than the other groups, these differences were not statistically significant (p=0.660 and p=0.647).ConclusionTopically applied HP in uncontrolled DM rats improved wound healing scores more than the non-diabetic controls. Metformin also significantly enhanced healing in DM rats, with results comparable to controls. Since HP and metformin are easily accessible, further research could lead to cost-effective treatments for wound healing issues in DM patients.